Proposta de implantação de estacionamento rotativo na região central do município de Alegre-ES - Amaral, Gabriela Senra (2019)
An increasingly used expression is Urban Mobility that is the movement of people from one point to another of the city, whether to work, study, shop or even for leisure. This displacement can be done on foot through non-motorized or motorized vehicles. However, with the development of cities after the period of urbanization, mobility problems began to emerge, due to the absence of urban planning policies associated with the increase in the vehicle fleet, as well as population growth. Among these problems is the public parking, so the objective of this work was to analyze the feasibility of installing a rotating parking system in the center of the city of Alegre-ES, aiming to improve traffic mobility and shorten the time spent searching for places. We detected inadequacies in the public parking in the Central region of Alegre, mainly regarding the time of vehicles in a vacancy, demonstrating that the implantation of the rotating parking is a viable alternative to the lack of vacancies in the current system. The proposed technical product of this work is the proposal to implement a rotating parking in the Center of Alegre-ES, in order to restore urban mobility in this region.